Lung Ultrasound to Detect Pneumothorax in Children Evaluated for Acute Chest Pain in the Emergency Department: An Observational Pilot Study - Scialanga, Barbara; Buonsenso, Danilo; Scateni, Simona; Valentini, Piero; Schingo, Paolo Maria Salvatore; Boccuzzi, Elena; Mesturino, Maria Alessia; Ferro, Valentina; Chiaretti, Antonio; Villani, Alberto; Supino, Maria Chiara; Musolino, Anna Maria (Frontiers in Pediatrics, 2022)
Background- Spontaneous pneumothorax is a relatively uncommon and poorly studied condition in children. While several protocols have been developed to evaluate the use of lung ultrasound for dyspneic adult patients in the emergency department, no specific guidelines are present for pediatric emergency physicians. Objectives- We prospectively analyzed children with acute chest pain and clinical suspicion of pneumothorax evaluated at the pediatric emergency department. Methods- After clinical examination and before chest x-ray, children underwent lung ultrasound to evaluate the presence of pneumothorax. We enrolled 77 children, 13 (16,9%) received a final diagnosis of pneumothorax. Results- In all 13 patients lung ultrasound showed the “bar-code sign” while in 12 (92,3%) there was the lung point, giving a diagnosis of pneumothorax. All cases were confirmed by chest x-ray. The lung point had a sensitivity of 92,3% and a specificity of 100% for the detection of pneumothorax. The “bar-code sign” had a sensitivity of 100% and a specificity of 100% for the detection of pneumothorax. Conclusion- Lung ultrasound is highly accurate in detecting or excluding pneumothorax in children with acute chest pain evaluated in the pediatric emergency department. Importantly, both lung-point and M-mode need to be performed when pneumothorax is suspected.